High level expression and purification of antimicrobial human cathelicidin LL-37 in Escherichia coli - Krahulec, Ján; Hyrsová, Marcela; Pepeliaev, Stanislav; Jílková, Jana; Cerný, Zbynek; Machálková, Jana (Applied microbiology and biotechnology, 2010)
The human antimicrobial peptide LL-37 is a cationic peptide with antimicrobial activity against both Gram-positive and Gram-negative microorganisms. This work describes the development of an expression system based on Escherichia coli capable of high production of the recombinant LL-37. The fusion protein Trx-LL-37 was expressed under control of T7 promoter. The expression of T7 polymerase in the E. coli strain constructed in this work was controlled by regulation mechanisms of the arabinose promoter. The expression plasmid was stabilized by the presence of parB locus which ensured higher homology of the culture during cultivation without antibiotic selection pressure. This system was capable of producing up to 1 g of fusion protein per 1 l of culture. The subsequent semipreparative HPLC allowed us to isolate 40 mg of pure LL-37. LL-37 showed high antimicrobial activity against both Gram-negative and Gram-positive microorganisms. Its activity against Candida albicans was practically nonexistent. Minimal Inhibition Concentration (MIC) determined for E. coli was 1.65 microM; for Staphylococcus aureus 2.31 microM, and for Enterococcus faecalis 5.54 microM. The effects of cathelicidin on E. coli included the ability to permeabilize both cell membranes, as could be observed by the increase of beta-galactosidase activity in extracellular space in time. Physiological changes were studied by scanning electron microscopy; Gram-positive microorganisms did not show any visible changes in cell shapes while the changes observed on E. coli cells were evident. The results of this work show that the herein designed expression system is capable of producing adequate quantities of active human antimicrobial peptide LL-37.
Keywords: Antimicrobial Cationic Peptides; Candida albicans; Bacteriophage T7; Promoter Regions, Genetic; Escherichia coli; Humans; rekombinantní fúzní proteiny; Staphylococcus aureus; kationické antimikrobiální peptidy; Enterococcus faecalis; DNA-Directed RNA Polymerases; virové proteiny; Microbial Sensitivity Tests; mikrobiální testy citlivosti; Chromatography, High Pressure Liquid; Viral Proteins; promotorové oblasti (genetika); DNA řízené RNA-polymerasy; vysokoúčinná kapalinová chromatografie; Gene Expression; lidé; bakteriofág T7; exprese genu; Recombinant Fusion Proteins